Pathways of nourishment and resilience: Advancing Indigenous Peoples' Food Systems in School Meals - Indigenous Peoples’ Food Systems Coalition Working Group on School Meals (Bioversity International and International Center for Tropical Agriculture, 2025)
Indigenous Peoples’ Food Systems (IPFS) are vital for sustaining biodiversity, cultural heritage, and resilient food systems, yet they are frequently marginalized in policies and programs and disproportionately affected by socio-economic and climate-related challenges. Paradoxically, these systems offer many solutions to global crises. School meals, the world’s largest safety net, currently nourish 407.8 million children worldwide. While their role in promoting education and child well-being is well recognized, their potential social and economic benefits—such as supporting local agriculture and preserving cultural traditions—are often overlooked. Integrating IPFS into school meal programs is a critical pathway to ensuring equitable access to nutritious and diverse foods. Prioritizing this integration strengthens food sovereignty, fosters intergenerational and intercultural knowledge exchange, and promotes public procurement of foods produced through agroecological and regenerative practices rooted in Indigenous traditions. This approach not only supports Indigenous livelihoods but also enhances biodiversity, resilience, and the sustainability of global food systems. This infographic builds on a brief that identifies barriers to Indigenous participation in school feeding supply chains and outlines strategies to overcome them through targeted policies and actions (https://hdl.handle.net/10568/175058). It was prepared for the 2nd School Meals Coalition Global Summit (18–19 September 2025), with graphic design by Luca Pierotti and Pablo Gallo.